Evaluating the Effects of the Conversation Media on the Representation Elements of Architectural Design for Improving User Participation - Ahmad Saleh (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
This paper evaluated the use of Three-dimensional (3D) Computer Visual (CV) media vs. Two-dimensional (2D) traditional Visual (TV) media as a conversation media on the representation elements of architectural design for improving user participation in the early stages of the design process. A qualitative experimental approach was adopted in this study. Data was collected from conversational dialogues between an architect and a list of clients. The results revealed that the 3D CV media was shown to be more supportive than 2D TV media in exploring representation elements and therefore to enhance the user participation. In addition, it reveals that the more complex the representational element, the greater the impact of 3D CV media compared to 2D TV media on user participation.